Gre factors prevent thermal and mechanical stresses induced by terahertz irradiation during transcription. (19th December 2020) - Imashimizu, Masahiko; Tanaka, Masahito; Hoshina, Hiromichi
Abstract: During transcription in cells, the transcription complex consisting of RNA polymerase, DNA and nascent RNA is exposed to fluctuating temperature and pressure. However, little is known about the mechanism of transcriptional homeostasis under fluctuating physical parameters. In this study, we generated these fluctuating parameters using pulsed local heating and acoustic waves in the reaction system of transcription by Escherichia coli RNA polymerase, using a terahertz free‐electron laser. We demonstrated that transcription processes, including abortive initiation and elongation pausing, and the fidelity of elongation are significantly affected by the laser‐based local perturbations. We also found that all these functional alternations in the transcription process are almost completely mitigated by the presence of Gre proteins. It is well known that Gre proteins enhance RNA cleavage of polymerase by binding to the pore structure termed secondary channel. Recently, the chaperone activities have also been proposed for Gre proteins, yet the details directly associated with transcription are largely unknown. Our finding indicates that Gre proteins are necessary for maintaining transcriptional homeostasis under thermal and mechanical stresses. Abstract : We generated fluctuating temperature and pressure using pulsed local heating and acoustic waves in the reaction system of transcription, using a terahertz free‐electron laser. We showed that transcription processes are significantly affected by the laser‐based local perturbations. These functional alternations in the transcription process are almost completely mitigated by the presence of Gre proteins.